FEATURES OF CONTRACEPTION IN WOMEN OF LATE REPRODUCTIVE AGE - Наталья Владимировна Артымук; Ольга Анатольевна Тачкова; Татьяна Юрьевна Марочко (The Publishing House Medicine and Enlightenment, 2020)
The aim of this study was to conduct an analytical review of modern scientific publications about features of contraception in women of advanced maternity age. Materials and methods. The analysis of 43 foreign and domestic literature sources on this topic has been carried out. Results. Despite the decline in fertility, women in the period of menopausal transition need contraception. The methods of choice are intrauterine and hormonal contraception, as well as surgical sterilization. After 50 years, hormonal contraception can include only progestogen-containing drugs; to prevent bone loss, DMPA should be stopped. Contraceptive methods can have therapeutic non-contraceptive effects, but their prescription should be based on health and likely risk factors. Since the risk of pregnancy becomes extremely low when a woman reaches the age of 55, contraception can be stop at this age even in menstruating women. Conclusion. Contraception in advanced maternity age has significant characteristics and should be recommended in accordance with the existing risk factors.